Seasonal prevalence, intensity and organal distribution of Helminth parasites in macrognathus aculeatus - Khanum, Hamida; Begum, Salma; Begum, Aleya (Dhaka University Journal of Biological Sciences, 2011)
Examination of 122 individuals of Macrognathus aculeatus (popularly known as Tara Baim), collected monthly, from the river Buriganga during March, 2007 to February, 2008 revealed 77 fishes were infected with various helminth parasites with an infection rate of 63.11% and intensity of infection of 3.18. A total of 245 parasites were recovered from different organs of the fishes, with the highest number from the intestine. Six species of helminths were detected, of which two were trematodes (Clinostomum piscidum and Rhynchooharynx paradoxa), one species of cestode (Marsipometra parva) and three species of nematodes (Pseudoproleptus vestibules, Cucullanus cirratus and Porrocaecum trichiuri L3 larva). The prevalence and intensity of parasitic infection were a bit higher in female fish than in male. The parasites were much more abundant in rainy season (75%) followed by summer (62.5%) and winter (31.81%). The larger fishes were heavily infected (71.01%) than medium (53.33%) and smaller (52.17%) fishes. Key words: Macrognathus aculeatus; Helminth; Prevalence; Intensity; Organal distribution; Seasonal variation DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8971 DUJBS 2011; 20(2): 117-122